2022
DOI: 10.1038/s41598-022-22605-2
|View full text |Cite
|
Sign up to set email alerts
|

Vibration analysis of a high-pressure multistage centrifugal pump

Abstract: High-pressure multistage centrifugal pumps have been widely used in modern industry and required low vibration and noise. In this study, modal analysis of the rotor system of a seven-stage centrifugal pump was carried out numerically by introducing fluid force to ensure that the centrifugal pump would not resonate. A vibration test bench was established to investigate the characteristics with flow rates of 0.8Qd, 1.0Qd, and 1.2Qd, and the vibration data of ten measuring points were collected. The period of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…With the development of computational fluid dynamics (CFD) technology, [11][12][13][14][15][16] researchers have conducted numerical simulations and experiments to study and reveal the influence of the clocking effect on flow characteristics in centrifugal pumps. Tan et al, 17 Zhu et al, 18 Jiang et al 19 studied the influence of the clocking effect in centrifugal pumps on flow characteristics and found that the relative angular position between the impeller and the diffuser significantly affects pump performance.…”
Section: Introductionmentioning
confidence: 99%
“…With the development of computational fluid dynamics (CFD) technology, [11][12][13][14][15][16] researchers have conducted numerical simulations and experiments to study and reveal the influence of the clocking effect on flow characteristics in centrifugal pumps. Tan et al, 17 Zhu et al, 18 Jiang et al 19 studied the influence of the clocking effect in centrifugal pumps on flow characteristics and found that the relative angular position between the impeller and the diffuser significantly affects pump performance.…”
Section: Introductionmentioning
confidence: 99%